2009
DOI: 10.2224/sbp.2009.37.10.1307
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mood States on Variety-Seeking Behavior: The Moderating Role of Price Promotion

Abstract: In this study we aimed to explore the effect of price promotion on the relationship between mood states and variety-seeking (VS) behavior. Participants were 133 university students, who were induced to feel either a sad or happy mood to test our hypothesis. Results indicated that price promotion mitigates the effect of affective states on VS. That is, people who are sad demonstrate more VS than those who are happy in the absence of price promotion. However, people in both mood states demonstrate similar level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…For example, a study with 124 subjects demonstrated that people are likely to include more variety in their consumption decisions when they are induced to a negative emotion than a positive emotion ( Chuang et al, 2008 ). Moreover, a series of research discussed the effect of two specific emotional states (sadness and happiness) on variety-seeking behaviors and found similar conclusions ( Lin and Lin, 2009 ; Chien-Huang and Hung-Chou, 2010 , 2012 ; Lin et al, 2011 ; Lin, 2014 ). These studies used choice task scenarios and revealed that participants with a sad mood selected more variety than those with a happy mood.…”
Section: Analysis and Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…For example, a study with 124 subjects demonstrated that people are likely to include more variety in their consumption decisions when they are induced to a negative emotion than a positive emotion ( Chuang et al, 2008 ). Moreover, a series of research discussed the effect of two specific emotional states (sadness and happiness) on variety-seeking behaviors and found similar conclusions ( Lin and Lin, 2009 ; Chien-Huang and Hung-Chou, 2010 , 2012 ; Lin et al, 2011 ; Lin, 2014 ). These studies used choice task scenarios and revealed that participants with a sad mood selected more variety than those with a happy mood.…”
Section: Analysis and Resultsmentioning
confidence: 88%
“…Then, researchers discussed how specific emotions and physical conditions, including positive and negative emotions ( Chuang et al, 2008 ), sadness and happiness ( Lin and Lin, 2009 ; Chien-Huang and Hung-Chou, 2010 , 2012 ; Lin et al, 2011 ; Lin, 2014 ), local optimism and pessimism ( Yang and Urminsky, 2015 ), and winning-losing perception ( Chang et al, 2021 ), affect consumers’ decision-making behaviors when faced with multiple choices. In these moods and states, seeking variety helps people change their current status.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, people in a negative mood may prefer a new option to the status quo because it has the potential to uplift their emotional state. For instance, Lin and Lin (2009) found that when choosing between hedonic goods such as food items, people show more variety-seeking behavior during a negative than a positive mood. This also resonates with the finding by Yen & Chuang (2008) that people in a negative mood are less willing to choose a status quo option, whereas people in a positive mood are more likely to choose a status quo option.…”
Section: Mood-maintenance Theorymentioning
confidence: 99%
“…Reflecting the importance of price promotions for firms, there is burgeoning research that addresses the effect of price promotions on brand evaluations (e.g., DelVecchio, Henard, and Freling 2006), repeat purchase (e.g., Ailawadi, Lehmann, and Neslin 2001), brand loyalty (e.g., Balachander, Ghosh, and Axel 2010), variety seeking (e.g., Lin and Lin 2009), and purchase amount (e.g., Manning and Sprott 2007). The central premise of these research studies is that price discounts have an effect on consumers who are concerned with only the economic value of the money saved.…”
mentioning
confidence: 99%